A Translation Analysis of Tourism Terms from Indonesian into English - Hertika Sianturi (Passage, 2013)
This research is entitled A Translation Analysis of Tourism Term from Indonesian Into English. The aim of the research is to discover the tourism terms found in the textbook, to examine the procedures of translation used in translating the Indonesian tourism terms into English, and to identify the quality of the tourism terms’ translation. This research employed a descriptive analysis with a qualitative approach as a method. It is based on Newmark’s theory on translation. There are 19 procedures of translation according to this theory; the translator in this study applied only 12 procedures in translating the tourism terms. Therefore, the quality of tourism terms’ translation in the bilingual textbook is in grade four or in excellent level. However, it can be proved that the transposition is the most frequently applied by the translator of the textbook in translating the tourism terms. It involves grammatical changes in translating tourism terms from Indonesian into English. On the other hand, the tourism textbook has many terms that require grammar changes in Bahasa Indonesia.Keywords: Tourism terms, Translation Procedures, Textbook